Pulmonary extraskeletal myxoid chondrosarcoma: A case report and literature review. (2016) - Balanzá, Ricardo; Arrangoiz, Rodrigo; Cordera, Fernando; Muñoz, Manuel; Luque-de-León, Enrique; Moreno, Eduardo; Molinar, Lourdes; Somerville, Nicole
Highlights: Extraskeletal myxoid chondrosarcoma (EMC) is a rare tumor characterized by the multinodular growth of primitive chondroid cells in an abundant myxoid matrix. EMC is categorized as a tumor of uncertain differentiation by the 2002 WHO classification. EMC has shown to have the recurrent balanced chromosomal translocation t(9;22) (q22;q12.2), which leads to the oncogenic fusion gene EWSR1-NR4A3. EMC usually presents in male patients beyond their fifth decade as a slow growing, palpable mass in the extremities. Pulmonary extraskeletal myxoid chondrosarcomas are extremely rare with only isolated case reports found in the literature. Abstract: Background: Extraskeletal myxoid chondrosarcoma (EMC) accounts for the 3% of all soft tissue sarcomas and it's categorized as a tumour of uncertain differentiation. This entity has shown to have the recurrent balanced chromosomal translocation t(9;22) (q22;q12.2), which leads to the oncogenic fusion gene EWSR1-NR4A3. This sarcoma usually presents as a slow growing, palpable mass in the extremities. EMC arising from the lung is extremely infrequent. We report one case of pulmonary extraskeletal mixoid chondrosarcoma and a review of the world literature. Case report: A 69-year-old male patient presented with intermittent hemoptysis for the last 6 months. A PET/CT scan showed a hypermetabolic solid mass with lobulated borders of approximately 29 × 26 mm in the inferior right lobe. We performed a right thoracotomy with inferior lobectomy and lymphadenectomy of levels VII, VIII, X, and XI levels. The neoplasm was constituted by cords of small cells with small round nucleus and scarce cytoplasm immerse in an abundant myxoid matrix. The immunophenotype was positive for MUM-1, CDK4, MDM2, and showed focal expression for S-100 protein and CD56. The final pathology report revealed a pulmonary extraskeletal mixoid chondrosarcoma. No further surgical interventions or adjuvant therapies were needed. Conclusion: EMC is an intermediate-grade neoplasm, characterized by a long clinical course with high potential for local recurrence and distant metastasis. Treatment for EMC is surgical and non-surgical treatment is reserved for recurrence or metastatic disease. Pulmonary extraskeletal myxoid chondrosarcoma is a rare neoplasm with only isolated case reports found in the literature.